The Role of Brown Adipose Tissue and Energy Metabolism in Mammalian Thermoregulation during the Perinatal Period - Cécile Bienboire-Frosini; Dehua Wang; Míriam Marcet-Rius; Dina Villanueva-García; Angelo Gazzano; Adriana Domínguez-Oliva; Adriana Olmos-Hernández; Ismael Hernández-Ávalos; Karina Lezama-García; Antonio Verduzco-Mendoza; Jocelyn Gómez-Prado; Daniel Mota-Rojas (Animals, 2023)
Hypothermia is one of the most common causes of mortality in neonates, and it could be developed after birth because the uterus temperature is more elevated than the extrauterine temperature. Neonates use diverse mechanisms to thermoregulate, such as shivering and non-shivering thermogenesis. These strategies can be more efficient in some species, but not in others, i.e., altricials, which have the greatest difficulty with achieving thermoneutrality. In addition, there are anatomical and neurological differences in mammals, which may present different distributions and amounts of brown fat. This article aims to discuss the neuromodulation mechanisms of thermoregulation and the importance of brown fat in the thermogenesis of newborn mammals, emphasizing the analysis of the biochemical, physiological, and genetic factors that determine the distribution, amount, and efficiency of this energy resource in newborns of different species. It has been concluded that is vital to understand and minimize hypothermia causes in newborns, which is one of the main causes of mortality in neonates. This would be beneficial for both animals and producers.